2008
DOI: 10.1590/s0102-09352008000200030
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e composição dos filés de jundiás (Rhamdia quelen) submetidos a diferentes dietas na fase de recria

Abstract: Desempenho e composição dos filés de jundiás (Rhamdia PL and PS diets (82.9 and 82.7%), and the lower fillet yield was observed in CL diet (34.1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(20 reference statements)
1
9
0
5
Order By: Relevance
“…In contrast, other studies have recently demonstrated a positive response between the presence of dietary carbohydrates with the production of amylolytic digestive enzymes, leading to different intermediate metabolism responses . Research on practical jundi a diets has focused on the evaluation of protein and lipid ingredients from plant origins, combined with animal sources, such as pork or bovine meat and bone meal (Coldebella & Rad€ unz Neto 2002;Lazzari et al 2008), since these are widely available in South Brazil, displaying good quality with competitive prices (Radunz Neto & Borba 2013).…”
Section: Ingredient Sources In Jundi a Dietsmentioning
confidence: 99%
“…In contrast, other studies have recently demonstrated a positive response between the presence of dietary carbohydrates with the production of amylolytic digestive enzymes, leading to different intermediate metabolism responses . Research on practical jundi a diets has focused on the evaluation of protein and lipid ingredients from plant origins, combined with animal sources, such as pork or bovine meat and bone meal (Coldebella & Rad€ unz Neto 2002;Lazzari et al 2008), since these are widely available in South Brazil, displaying good quality with competitive prices (Radunz Neto & Borba 2013).…”
Section: Ingredient Sources In Jundi a Dietsmentioning
confidence: 99%
“…Para o jundiá, o uso de farinha de carne e ossos, combinada com farelo de soja, na dieta, tem se mostrado eficiente (Lazzari et al 2008).…”
Section: Key-wordsunclassified
“…taram melhor TCE, quando alimentados com dietas contendo farinha de peixe + farelo de soja (2,2 ± 0,1) e farinha de carne e ossos + farelo de soja (2,1 ± 0,1) (Lazzari et al 2008), sendo que estes valores foram semelhantes aos encontrados neste trabalho. A disponibilidade de juvenis em quantidade e qualidade é considerada um ponto crítico, para o sucesso da piscicultura, em que a nutrição é o principal fator responsável por erros frequentes em larvicultura, limitando a expansão da atividade (Prieto & Atencio 2009).…”
Section: Variávelunclassified
See 1 more Smart Citation
“…Tal comportamento se assemelha ao de alguns peixes onívoros e, principalmente, ao de carnívoros, o que o torna um peixe de hábito alimentar onívoro, com tendência à carnivoria (Oliveira Filho & Fracalossi, 2006). Contudo, o jundiá não depende totalmente da farinha de peixe da dieta, pois aceita dietas exclusivamente vegetais ou compostas de vegetais com farinhas de origem animal (Coldebella & Radünz Neto, 2002;Lazzari et al, 2008).…”
Section: Introductionunclassified